Fabrication of functional and nano-biocomposite scaffolds using strontium-doped bredigite nanoparticles/polycaprolactone/poly lactic acid via 3D printing for bone regeneration - Nadi, Akram; Khodaei, Mohammad; Javdani, Moosa; Mirzaei, Seyed Abbas; Soleimannejad, Mostafa; Tayebi, Lobat; Asadpour, Shiva (International journal of biological macromolecules, 2022)
Bone tissue engineering is a field to manufacture scaffolds for bone defects that cannot repair without medical interventions. Ceramic nanoparticles such as bredigite have importance roles in bone regeneration. We synthesized a novel strontium (Sr) doped bredigite (Bre) nanoparticles (BreSr) and then developed new nanocomposite scaffolds using polycaprolactone (PCL), poly lactic acid (PLA) by the 3D-printing technique. Novel functional nanoparticles were synthesized and characterized using field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and energy dispersive spectroscopy (EDS: map). The nanoparticles were uniformly distributed in the polymer matrix composites. The 3D- printed scaffolds were investigated using scanning electron microscopy (SEM), X-ray diffraction (XRD), attenuated total reflection-fourier transform infrared (ATR-FTIR), degradation rate porosity, mechanical tests, apatite formation and cell culture. Degradation rate and mechanical strength were increased in the PLA/PCL/Bre-5%Sr nanocopmposite scaffolds. Hydroxyapatite crystals were also created on the scaffold surface in the bioactivity test. The scaffolds supported viability and proliferation of human osteoblasts. Gene expression and calcium deposition in the samples containing nanoparticles indicated statistical different than the scaffolds without nanoparticles. The nanocomposite scaffolds were implanted into the critical-sized calvarial defects in rat for 3 months. The scaffolds containing Bre-Sr ceramic nanoparticles exhibited the best potential to regenerate bone tissue.Bone tissue engineering is a field to manufacture scaffolds for bone defects that cannot repair without medical interventions. Ceramic nanoparticles such as bredigite have importance roles in bone regeneration. We synthesized a novel strontium (Sr) doped bredigite (Bre) nanoparticles (BreSr) and then developed new nanocomposite scaffolds using polycaprolactone (PCL), poly lactic acid (PLA) by the 3D-printing technique. Novel functional nanoparticles were synthesized and characterized using field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), and energy dispersive spectroscopy (EDS: map). The nanoparticles were uniformly distributed in the polymer matrix composites. The 3D- printed scaffolds were investigated using scanning electron microscopy (SEM), X-ray diffraction (XRD), attenuated total reflection-fourier transform infrared (ATR-FTIR), degradation rate porosity, mechanical tests, apatite formation and cell culture. Degradation rate and mechanical strength were increased in the PLA/PCL/Bre-5%Sr nanocopmposite scaffolds. Hydroxyapatite crystals were also created on the scaffold surface in the bioactivity test. The scaffolds supported viability and proliferation of human osteoblasts. Gene expression and calcium deposition in the samples containing nanoparticles indicated statistical different than the scaffolds without nanoparticles. The nanocomposite scaffolds were implanted into the critical-sized calvarial defects in rat for 3 months. The scaffolds containing Bre-Sr ceramic nanoparticles exhibited the best potential to regenerate bone tissue.